Assessment and Critique of the Judgments, Epistemology and Light System in the Philosophy of Eshraq - Zohreh Saeidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Philosophy of Eshraq is represented as new and illustrative thought in the history of Islamic philosophy.  Studying Islamic philosophy is not completed without studying Philosophy of Eshraq. The book describes and analyzes wisdom of Eshraq as illuminating fundamental principles of the Eshraq Philosophy.  The current book describes and analyzes Philosophy of Eshraq  concentrating on “Hikmat  al – Eshraq” book. For this purpose, the author has offered judgments of Sheikh Eshraq about subjects of the philosophy that are considered as Sheikh Eshraq replies to Masha, and he has analyzed them.  In this article, we introduce the book and indicate backgrounds of such books and analyze its content and formal dimensions. In order to do provide the assessment and critique, we indicate negative and positive aspects and suggest some recommendations to improve the book in the subsequent editions.